The Retarded Acceptance of the Marginal Utility Theory: The Schumpeter Prize Fund (Quarterly Journal of Economics, 1955)
The Schumpeter Prize Fund Get access The Quarterly Journal of Economics, Volume 69, Issue 3, August 1955, Pages 478–479, https://doi.org/10.2307/1885855 Published: 01 August 1955